e-skills, soft skills & social skills - students' competences on a digital age - Messias, Inês (2022)
The demands on today‟s digital society raise the necessity of students to acquire different skills and competences - a new kind of literacy. Besides digital skills, there is also the need of being in possess of social and soft skills. Learning, due to the advent of social Web and collaborative virtual environments, has a lot to do with socialization. This article aims to know if and how these competences and access to digital and virtual tools can change students learning processes, allowing them to be more participative in constructing their knowledge.